The characterization of androstenone transport in boar plasma. Issue 185 (January 2019) - Bone, Christine; Anderson, Courtney; Lou, Yanping; Squires, E.J.
Highlights: Androstenone circulates in the blood bound non-specifically to plasma proteins. DHEA demonstrates a greater binding efficiency for plasma proteins than androstenone. The transport of androstenone and DHEA is primarily facilitated by albumin. There is a lack of biological variability in androstenone transport. Abstract: The transport of steroids by plasma proteins influences the amount of steroid available for uptake by the target tissue. In the boar, androstenone is transported to the adipose tissue where it accumulates to cause an off-odour or off-flavour in pork, known as boar taint. The mechanism of the transport of androstenone in the boar remains unclear, and the plasma protein responsible for binding androstenone has yet to be identified. Therefore, the purpose of the present study was to characterize the binding of androstenone to plasma proteins in the boar. The binding specificity of androstenone to plasma proteins was first investigated using a HPLC gel filtration method. [ 3 H]-androstenone was incubated with plasma in the presence or absence of unlabeled competitors and the displacement of androstenone from plasma proteins was measured. In the presence of excess unlabeled competitors, [ 3 H]-androstenone was only partially displaced from plasma proteins, indicating it binds to a low affinity high capacity plasma protein. Binding kinetics studies were also conducted to characterize the binding of androstenone and dehydroepiandrosterone (DHEA) to plasma proteins. The Bmax of androstenone and DHEA was approximately the same (89.1% and 92.3%, respectively). However, the binding affinity ( K ) of androstenone was 6.5 fold greater than DHEA (0.39 nmol/ml and 0.06 nmol/ml, respectively). Affinity chromatography was used to remove albumin from the plasma proteins. Following incubations with androstenone and DHEA, the binding observed in the albumin free protein fraction was reduced 2.6 and 2.1 fold, respectively relative to the binding in the albumin protein fractions. These results provide direct evidence that androstenone is transported non-specifically by albumin in the plasma of the boar.